ECMO in neonates: The association between cerebral hemodynamics with neurological function - Yu, Shu-Han; Mao, Dan-Hua; Ju, Rong; Fu, Yi-Yong; Zhang, Li-Bing; Yue, Guang (Frontiers in Pediatrics, 2022)
Extracorporeal membrane oxygenation (ECMO) is a superior life support technology, commonly employed in critical patients with severe respiratory or hemodynamic failure to provide effective respiratory and circulatory support, which is especially recommended for the treatment of critical neonates. However, the vascular management of neonates with veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is still under controversy. Reconstruction or ligation for the right common carotid artery (RCCA) after ECMO is inconclusive. This review summarized the existed studies on hemodynamics and neurological function after vascular ligation or reconstruction hoping to provide better strategies for vessel management in newborns after ECMO. After reconstruction, the right cerebral blood flow can increase immediately, and the normal blood supply can be restored rapidly. But the reconstructed vessel may be occluded and stenotic in long-term follow-ups. Ligation may cause lateralization damage, but there could be no significant effect owing to the establishment of collateral circulation. The completion of the circle of Willis, the congenital anomalies of cerebral or cervical vasculature, the duration of ECMO, and the vascular condition at the site of arterial catheterization should be assessed carefully before making the decision. It is also necessary to follow up on the reconstructed vessel sustainability, and the association between cerebral hemodynamics and neurological function requires further large-scale multi-center studies.